Gerakan Menanam Sayur Bersama PKK Karang Wetan Genuk Kabupaten Semarang - Zumrotul Chaerijah; Puji Purwaningsih (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
One way to raise awareness of love for the environment and food security is by planting vegetable plants. Currently, the vegetable planting movement is an effort to control regional inflation. Prevention of price spikes in vegetable commodities is an important aspect in household life, so the vegetable planting movement is a strategic step in the Family Welfare Empowerment Movement. The extension method was chosen in this community service. Analysis using the Wilcoxon test showed that the p value (0.000) showed that there was an increase in knowledge between before and after the counseling.